Effect of Salicylic Acid on Physico-chemical Attributes and Shelf Life of Tomato Fruits at Refrigerated Storage - Mandal, Debashis; Pautu, Lalhlimpuii; Hazarika, Tridip Kumar; Nautiyal, Bhagwati Prasad; Shukla, Amritesh Chandra (International Journal of Bio-resource and Stress Management, 2016)
Tomato, the frequently consumed solanecous fruit vegetable faced rapid deterioration of fruit edible quality under ambient storage and though refrigerated storage has proved better retention but mostly with the outbreak of chilling injury. Therefore, attempt with salicylic acid, a safe phenolic having identified anti-ethylene effect, has been made during this study to evaluate its effect on shelf life and quality attributes of tomato fruit in refrigerated storage. Fruits of tomato variety Samrudhi at pink to light red stage were treated with different concentration of salicylic acid (0.2−1.2 mM) along with control (water dipped) and were kept at 4−5 °C with 65−80% relative humidity in four replications following complete randomized design. Results showed salicylic acid (SA) treated fruits had better keeping quality than control though in concentration dependant manner. At 21 days after storage (DAS), fruits kept in control condition lost 13.69% of weight compared with the fruits treated with SA at 1.2 mM (5.79%). SA at 1-1.2 mM significantly reduced chilling injury (Chilling Injury Index/CII: 1.44−2.88) compared with fruits at control (CII: 4.98). Fruits at control showed deterioration in sugar content along with acidity and ascorbic acid. Further, it took rapid increase in pigment whereas, SA treated fruit in relatively higher concentration (0.8−1.2 mM), maintained fruit quality attributes with consistent intensification of carotenoids and lycopene even at 21 DAS. SA at 1.2 mM recorded maximum shelf life (32.75 days) to be considered as the best treatment having high maintenance of fruit edible qualities.